Resultados do ENADE 2012: contribuições ao curso de logística da Universidade Federal do Tocantins. - Guimarães, Lucivânia Maria (Universidade Federal do Tocantins, 2020)
The this study is to produce contributions to the Logistics Course of the Federal University of Tocantins (UFT) from the course report of the National Student Performance Examination (Enade) 2012. The Examination is operationalized through the students' test performance; Students' perception of the test; And, student questionnaire analysis results. These results can be useful to guide the pedagogical and administrative actions of the course, since they are important references for the knowledge of the institutional reality and for the permanent search of the improvement of the graduation quality, aspects that evidence the integrative character inherent to the evaluation. The research is qualitative, descriptive, documentary, with deductive method. Among the results we find students' responses, saying that they "do not know the content" of the Enade test, or that there is "a different way of approaching content". Among other contributions made, it is necessary to create a diagnosis to know the specific causes of students' difficulties in relation to general and specific training content; And, to create an instrument to evaluate the contents worked in the disciplines, since many students claim ignorance of the content of the test of the Enade.